Preparation method of gradient transition type Zn / Co core-shell MOF catalyst and gradient transition type Zn / Co core-shell MOF catalyst
By constructing a three-layer structure of the gradient transition Zn/Co core-shell MOF catalyst, the problems of low activity, poor selectivity and insufficient stability in the CO2 hydrogenation reaction are solved, and efficient and stable methanol preparation is achieved.
Patent Information
- Application Number
- CN202411807672.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-10
AI Technical Summary
Traditional Cu-based catalysts have problems such as low activity, poor selectivity and insufficient stability in CO2 hydrogenation reaction, which is difficult to meet the needs of industrial applications.
Using a gradient transition Zn/Co core-shell MOF catalyst, a three-layer structure of ZIF-8 core, ZIF-67 shell and gradient transition zone is constructed to achieve continuous changes in the Zn/Co ratio and form an active center of synergistic effects.
It has achieved high methanol selectivity, excellent low-temperature activity, excellent long-term stability and efficient CO2 conversion, which is significantly better than traditional catalysts.
Smart Images

Figure BDA0005179710080000141 
Figure BDA0005179710080000142
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of MOF catalysts, and in particular to a preparation method of a gradient transition type Zn / Co core-shell MOF catalyst and a gradient transition type Zn / Co core-shell MOF catalyst. Background Art
[0002] As the world faces the dual challenges of climate change and energy transformation, the resource utilization of carbon dioxide has received increasing attention. Among them, CO2 hydrogenation to methanol can not only achieve carbon recycling, but also provide a way to store chemical energy for renewable energy, so it has become a research hotspot. However, traditional Cu-based catalysts face problems such as low activity, poor selectivity, and insufficient stability in CO2 hydrogenation reactions, making it difficult to meet the needs of industrial applications.
[0003] In recent years, metal organic framework (MOF) materials have shown great potential in the field of catalysis due to their high specific surface area, tunable pore structure and abundant active sites. In particular, ZIF-8 and ZIF-67, as typical zeolitic imidazolate framework materials, have high specific surface area and excellent catalytic activity, respectively, and have become the focus of researchers. However, a single ZIF material often cannot take into account both high adsorption performance and high catalytic activity.
[0004] In order to overcome the limitations of single MOF materials, researchers have tried a variety of strategies, such as constructing core-shell structures and introducing bimetallic centers. Although these methods have improved the catalytic performance to a certain extent, they still have the following problems: 1) There is an obvious interface between the core and the shell in the traditional core-shell structure, which is prone to structural instability due to lattice mismatch; 2) Simple bimetallic mixing is difficult to maximize the synergistic effect of the metal center; 3) The distribution of active components is uneven, resulting in low catalyst utilization.
[0005] Therefore, there is an urgent need to develop a new type of MOF catalyst that can simultaneously achieve high adsorption performance, high catalytic activity and high stability to meet the stringent requirements of CO2 hydrogenation to methanol reaction. Summary of the invention
[0006] The gradient transition Zn / Co core-shell MOF catalyst proposed by the present invention is designed to solve the above problems.
[0007] The object of the present invention is to provide a method for preparing a gradient transition Zn / Co core-shell MOF catalyst, comprising the following steps:
[0008] (1) Preparation of ZIF-8 core material, the specific steps are as follows:
[0009] a) First, add 100-300 parts by weight of methanol into a 500 mL round-bottom flask;
[0010] b) secondly, adding 10-30 parts by weight of zinc nitrate hexahydrate to the methanol under continuous stirring, and stirring at 20-25° C. for 30-60 minutes;
[0011] c) Then, in another 500 mL flask, add 100-300 parts by weight of methanol and then add 20-60 parts by weight of 2-methylimidazole, and stir at 20-25° C. for 30-60 minutes;
[0012] d) then, slowly adding the 2-methylimidazole solution to the zinc nitrate solution at a rate of 2-5 mL / min, and after the addition is completed, continuing to stir at 20-25° C. for 2-4 hours;
[0013] e) again, centrifuging the obtained suspension and washing it three times with methanol;
[0014] f) finally, the washed solid is dried under vacuum at 60-80° C. for 12-24 hours to obtain the ZIF-8 core material;
[0015] (2) Preparation of gradient transition Zn / Co core-shell MOF, the specific steps are as follows:
[0016] a) First, in a 1000 mL three-necked flask, 200-400 parts by weight of methanol and 10-30 parts by weight of the ZIF-8 core material were added;
[0017] b) Next, in another 250 mL flask, dissolve 5-25 parts by weight of cobalt nitrate hexahydrate and 10-50 parts by weight of 2-methylimidazole in 50-100 parts by weight of methanol;
[0018] c) Then, the three-necked flask was placed in a constant temperature water bath at 30-50° C. and stirred at a speed of 300-500 rpm;
[0019] d) then, slowly adding the mixed solution of cobalt nitrate and 2-methylimidazole at a rate of 0.5-2 mL / min;
[0020] e) again, when the pH value drops to 5.5-6.5, 0.5-5 parts by weight of triethylamine is slowly added dropwise to adjust the pH value to 7.0-8.0;
[0021] f) continuing to react at 30-50° C. for 4-8 hours;
[0022] g) Subsequently, the reaction mixture was cooled to room temperature, centrifuged, and washed three times with methanol;
[0023] h) Finally, the washed solid is vacuum dried at 60-80° C. for 12-24 hours to obtain a gradient transition Zn / Co core-shell MOF catalyst.
[0024] Preferably, in step (1) d), the stirring speed is 300-500 rpm.
[0025] Preferably, in step (1) e), the rotation speed of the centrifugal separation is 6000-8000 rpm and the time is 10-15 minutes.
[0026] Preferably, in step (2) g), the rotation speed of the centrifugal separation is 6000-8000 rpm, and the time is 10-15 minutes.
[0027] The preparation method described herein obtains a gradient transition type Zn / Co core-shell MOF catalyst.
[0028] A gradient transition type Zn / Co core-shell MOF catalyst comprises a ZIF-8 core, a ZIF-67 shell layer and a gradient transition zone between the ZIF-8 core and the ZIF-67 shell layer.
[0029] Preferably, the ZIF-8 core is prepared by reacting 10-30 parts by weight of zinc nitrate hexahydrate and 20-60 parts by weight of 2-methylimidazole.
[0030] Preferably, the ZIF-67 shell is prepared by reacting 5-25 parts by weight of cobalt nitrate hexahydrate and 10-50 parts by weight of 2-methylimidazole.
[0031] Preferably, the atomic ratio of Zn and Co in the gradient transition zone changes gradually from the core to the shell.
[0032] The application of the gradient transition Zn / Co core-shell MOF catalyst in the CO2 hydrogenation to methanol reaction.
[0033] By ingeniously constructing a three-layer structure of ZIF-8 core, ZIF-67 shell and gradient transition zone, the present invention achieves the following innovations:
[0034] 1. Introduction of gradient transition structure: By precisely controlling the synthesis conditions, a transition zone with a continuously changing Zn / Co ratio is formed between the ZIF-8 core and the ZIF-67 shell. This structure not only relieves the lattice stress at the core-shell interface, but also provides abundant synergistic active sites for the reaction.
[0035] 2. Maximization of Zn / Co synergistic effect: Zn in the gradient transition zone 2+ and Co 2+ The ratio of ions changes continuously, forming a series of active centers with different electronic structures. This unique electronic structure is conducive to the adsorption and activation of CO2, and provides ideal stabilization energy for the reaction intermediates.
[0036] 3. Multi-scale structural design: The ZIF-8 core provides a high specific surface area and selective adsorption sites, which are beneficial to the enrichment of reactants; the ZIF-67 shell provides stability and catalytic active sites; the gradient transition zone achieves seamless connection and performance synergy between the two.
[0037] From the perspective of molecular orbital theory, Zn 2+ The filled d orbitals and Co 2+ There may be electron transfer between the unfilled d orbitals of Zn1-xCox, which may regulate the electron density of the active site, thereby optimizing the adsorption strength and activation energy barrier of CO2. At the same time, the Zn1-xCox mixed metal sites formed in the gradient transition region may have a unique orbital energy level distribution, providing an ideal electronic environment for the activation of CO2 and the production of methanol.
[0038] In addition, the controlled kinetic deposition strategy adopted by the present invention achieves directional migration and rearrangement of metal ions by precisely controlling the reaction temperature, pH value and precursor concentration. This method not only ensures the formation of a gradient transition structure, but also improves the overall uniformity and stability of the catalyst.
[0039] Based on the above innovative design, the gradient transition Zn / Co core-shell MOF catalyst of the present invention exhibits the following outstanding beneficial effects:
[0040] 1. Ultra-high methanol selectivity: Under mild conditions of 250°C and 5MPa, the methanol selectivity is as high as 73.6%, far exceeding traditional Cu-based catalysts.
[0041] 2. Excellent low-temperature activity: It still exhibits high activity at relatively low temperatures, which is beneficial to reducing energy consumption and improving the thermodynamic advantage of the reaction.
[0042] 3. Excellent long-term stability: After 100 hours of continuous reaction, the activity only decreases by 5%, which is significantly better than traditional catalysts.
[0043] 4. Efficient CO2 conversion: The CO2 conversion rate reaches 29.1%, and the methanol space-time yield is as high as 436g / (kg·h), showing potential for industrial application.
[0044] 5. Structural adjustability: By changing the synthesis conditions, the structure of the gradient transition zone can be flexibly controlled, providing design ideas for other catalytic reactions.
[0045] In summary, the gradient transition Zn / Co core-shell MOF catalyst proposed in this invention not only solves the problems faced by traditional MOF materials in the CO2 hydrogenation to methanol reaction, but also achieves synergistic improvement of multiple performances through ingenious structural design. This new catalyst structure opens up a new path for the application of MOF materials in the field of catalysis, and also provides a powerful tool for addressing global climate change and energy transformation. DETAILED DESCRIPTION
[0046] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0047] Example 1: Preparation of gradient transition Zn / Co core-shell MOF catalyst
[0048] This embodiment provides a gradient transition type Zn / Co core-shell MOF catalyst and a preparation method thereof. The catalyst comprises a ZIF-8 core, a ZIF-67 shell layer and a gradient transition zone between the two. The preparation method comprises the following steps:
[0049] (1) Preparation of ZIF-8 core material:
[0050] First, 100 parts by weight of methanol were added to a 500 mL round-bottom flask. Secondly, 10 parts by weight of zinc nitrate hexahydrate were added to the methanol under continuous stirring (300 rpm) and stirred at 20 ° C for 30 minutes. Then, in another 500 mL flask, 100 parts by weight of methanol were added, and 20 parts by weight of 2-methylimidazole were added and stirred at 20 ° C for 30 minutes. Next, the 2-methylimidazole solution was slowly added dropwise to the zinc nitrate solution at a rate of 2 mL / min. After the addition was completed, stirring was continued at 20 ° C for 2 hours. Again, the obtained suspension was centrifuged (6000 rpm, 10 minutes) and washed 3 times with methanol, 50 mL each time. Finally, the washed solid was vacuum dried at 60 ° C for 12 hours to obtain the ZIF-8 core material.
[0051] (2) Preparation of gradient transition Zn / Co core-shell MOF:
[0052] First, in a 1000mL three-necked flask, 200 parts by weight of methanol and 10 parts by weight of the ZIF-8 core material were added. Secondly, in another 250mL flask, 5 parts by weight of cobalt nitrate hexahydrate and 10 parts by weight of 2-methylimidazole were dissolved in 50 parts by weight of methanol. Then, the three-necked flask was placed in a 30°C constant temperature water bath with a stirring speed of 300rpm. Next, a mixed solution of cobalt nitrate and 2-methylimidazole was slowly added dropwise at a rate of 0.5mL / min. Again, when the pH value dropped to 5.5, 0.5 parts by weight of triethylamine was slowly added dropwise to adjust the pH value to 7.0. Continue to react at 30°C for 4 hours. Subsequently, the reaction mixture was cooled to room temperature, centrifuged (6000rpm, 10 minutes), and washed 3 times with methanol, 100mL each time. Finally, the washed solid was vacuum dried at 60°C for 12 hours to obtain a gradient transition Zn / Co core-shell MOF catalyst.
[0053] Example 2: Preparation of gradient transition Zn / Co core-shell MOF catalyst
[0054] This embodiment provides another gradient transition Zn / Co core-shell MOF catalyst and its preparation method. The preparation method comprises the following steps:
[0055] (1) Preparation of ZIF-8 core material:
[0056] First, 200 parts by weight of methanol were added to a 500 mL round-bottom flask. Secondly, 20 parts by weight of zinc nitrate hexahydrate were added to the methanol under continuous stirring (400 rpm), and stirred at 22.5 ° C for 45 minutes. Then, in another 500 mL flask, 200 parts by weight of methanol were added, and 40 parts by weight of 2-methylimidazole were added, and stirred at 22.5 ° C for 45 minutes. Then, the 2-methylimidazole solution was slowly added dropwise to the zinc nitrate solution at a rate of 3.5 mL / min, and after the addition was completed, stirring was continued for 3 hours at 22.5 ° C. Again, the obtained suspension was centrifuged (7000 rpm, 12.5 minutes) and washed 3 times with methanol, 75 mL each time. Finally, the washed solid was vacuum dried at 70 ° C for 18 hours to obtain the ZIF-8 core material.
[0057] (2) Preparation of gradient transition Zn / Co core-shell MOF:
[0058] First, in a 1000mL three-necked flask, 300 parts by weight of methanol and 20 parts by weight of the ZIF-8 core material were added. Secondly, in another 250mL flask, 15 parts by weight of cobalt nitrate hexahydrate and 30 parts by weight of 2-methylimidazole were dissolved in 75 parts by weight of methanol. Then, the three-necked flask was placed in a 40°C constant temperature water bath with a stirring speed of 400rpm. Next, a mixed solution of cobalt nitrate and 2-methylimidazole was slowly added dropwise at a rate of 1.25mL / min. Again, when the pH value dropped to 6.0, 2.75 parts by weight of triethylamine were slowly added dropwise to adjust the pH value to 7.5. Continue to react at 40°C for 6 hours. Subsequently, the reaction mixture was cooled to room temperature, centrifuged (7000rpm, 12.5 minutes), and washed 3 times with methanol, 150mL each time. Finally, the washed solid was vacuum dried at 70°C for 18 hours to obtain a gradient transition Zn / Co core-shell MOF catalyst.
[0059] Example 3: Preparation of gradient transition Zn / Co core-shell MOF catalyst
[0060] This embodiment provides a third gradient transition Zn / Co core-shell MOF catalyst and a preparation method thereof. The preparation method comprises the following steps:
[0061] (1) Preparation of ZIF-8 core material:
[0062] First, 300 parts by weight of methanol were added to a 500 mL round-bottom flask. Secondly, 30 parts by weight of zinc nitrate hexahydrate were added to the methanol under continuous stirring (500 rpm) and stirred at 25 ° C for 60 minutes. Then, in another 500 mL flask, 300 parts by weight of methanol were added, and 60 parts by weight of 2-methylimidazole were added and stirred at 25 ° C for 60 minutes. Next, the 2-methylimidazole solution was slowly added dropwise to the zinc nitrate solution at a rate of 5 mL / min, and after the addition was completed, stirring was continued at 25 ° C for 4 hours. Again, the obtained suspension was centrifuged (8000 rpm, 15 minutes) and washed 3 times with methanol, 100 mL each time. Finally, the washed solid was vacuum dried at 80 ° C for 24 hours to obtain the ZIF-8 core material.
[0063] (2) Preparation of gradient transition Zn / Co core-shell MOF:
[0064] First, in a 1000mL three-necked flask, 400 parts by weight of methanol and 30 parts by weight of the ZIF-8 core material were added. Secondly, in another 250mL flask, 25 parts by weight of cobalt nitrate hexahydrate and 50 parts by weight of 2-methylimidazole were dissolved in 100 parts by weight of methanol. Then, the three-necked flask was placed in a 50°C constant temperature water bath with a stirring speed of 500rpm. Next, a mixed solution of cobalt nitrate and 2-methylimidazole was slowly added dropwise at a rate of 2mL / min. Again, when the pH value dropped to 6.5, 5 parts by weight of triethylamine were slowly added dropwise to adjust the pH value to 8.0. Continue to react at 50°C for 8 hours. Subsequently, the reaction mixture was cooled to room temperature, centrifuged (8000rpm, 15 minutes), and washed 3 times with methanol, 200mL each time. Finally, the washed solid was vacuum dried at 80°C for 24 hours to obtain a gradient transition Zn / Co core-shell MOF catalyst.
[0065] Example 4: Preparation of gradient transition Zn / Co core-shell MOF catalyst
[0066] This embodiment provides a fourth gradient transition Zn / Co core-shell MOF catalyst and a preparation method thereof. The preparation method comprises the following steps:
[0067] (1) Preparation of ZIF-8 core material:
[0068] First, 250 parts by weight of methanol were added to a 500 mL round-bottom flask. Secondly, 25 parts by weight of zinc nitrate hexahydrate were added to the methanol under continuous stirring (450 rpm), and stirred at 23.5 ° C for 50 minutes. Then, in another 500 mL flask, 250 parts by weight of methanol were added, and 50 parts by weight of 2-methylimidazole were added, and stirred at 23.5 ° C for 50 minutes. Then, the 2-methylimidazole solution was slowly added dropwise to the zinc nitrate solution at a rate of 4 mL / min, and after the addition was completed, stirring was continued at 23.5 ° C for 3.5 hours. Again, the obtained suspension was centrifuged (7500 rpm, 13 minutes) and washed 3 times with methanol, 85 mL each time. Finally, the washed solid was vacuum dried at 75 ° C for 20 hours to obtain the ZIF-8 core material.
[0069] (2) Preparation of gradient transition Zn / Co core-shell MOF:
[0070] First, in a 1000mL three-necked flask, 350 parts by weight of methanol and 25 parts by weight of the ZIF-8 core material were added. Secondly, in another 250mL flask, 20 parts by weight of cobalt nitrate hexahydrate and 40 parts by weight of 2-methylimidazole were dissolved in 85 parts by weight of methanol. Then, the three-necked flask was placed in a 45°C constant temperature water bath with a stirring speed of 450rpm. Next, a mixed solution of cobalt nitrate and 2-methylimidazole was slowly added dropwise at a rate of 1.75mL / min. Again, when the pH value dropped to 6.25, 3.75 parts by weight of triethylamine were slowly added dropwise to adjust the pH value to 7.75. Continue to react at 45°C for 7 hours. Subsequently, the reaction mixture was cooled to room temperature, centrifuged (7500rpm, 13 minutes), and washed 3 times with methanol, 175mL each time. Finally, the washed solid was vacuum dried at 75°C for 20 hours to obtain a gradient transition Zn / Co core-shell MOF catalyst.
[0071] Preferably, in an embodiment of the present invention, the ZIF-8 core provides a high specific surface area and selective adsorption sites, which are conducive to the enrichment and preliminary activation of reactants. The ZIF-67 shell provides stability and catalytic active sites, wherein the variable valence of Co ions is conducive to the catalytic reaction. The gradient transition zone realizes the synergistic catalytic effect of Zn and Co ions, and significantly improves the stability and catalytic performance of the material by alleviating the lattice mismatch of the core-shell interface.
[0072] In addition, by precisely controlling the reaction temperature and pH value, the present invention realizes the directional migration and rearrangement of metal ions, forming a core-shell structure with continuous component distribution. This structure not only avoids the mutation at the interface in the traditional core-shell structure, but also facilitates the improvement of electron transport and catalytic activity. From the perspective of molecular orbital theory, Co 2+ The unfilled 3d orbitals of Zn 2+ The filled 3d orbitals interact with each other to form new molecular orbitals, which may be the source of the synergistic catalytic effect.
[0073] Through the preparation method of the above embodiment, a gradient transition Zn / Co core-shell MOF catalyst with excellent catalytic performance can be obtained. The catalyst exhibits excellent catalytic activity and selectivity in reactions such as CO2 hydrogenation to methanol, opening up a new path for the application of MOF materials in the field of catalysis.
[0074] Comparative Example 1: Preparation of a single ZIF-8 catalyst
[0075] This comparative example is intended to demonstrate the superiority of the gradient transition Zn / Co core-shell structure. The preparation method is the same as the ZIF-8 core material preparation steps of Example 1, but the subsequent ZIF-67 shell preparation is not performed. The specific steps are as follows:
[0076] 100 parts by weight of methanol were added to a 500 mL round-bottom flask. Under continuous stirring (300 rpm), 10 parts by weight of zinc nitrate hexahydrate were added to the methanol and stirred at 20 ° C for 30 minutes. Then, in another 500 mL flask, 100 parts by weight of methanol were added, and 20 parts by weight of 2-methylimidazole were added, and stirred at 20 ° C for 30 minutes. Next, the 2-methylimidazole solution was slowly added dropwise to the zinc nitrate solution at a rate of 2 mL / min. After the addition was completed, stirring was continued at 20 ° C for 2 hours. Again, the obtained suspension was centrifuged (6000 rpm, 10 minutes) and washed 3 times with methanol, 50 mL each time. Finally, the washed solid was vacuum dried at 60 ° C for 12 hours to obtain a ZIF-8 catalyst.
[0077] Comparative Example 2: Preparation of a single ZIF-67 catalyst
[0078] This comparative example is intended to demonstrate the importance of Zn / Co synergy. The preparation method refers to the ZIF-67 shell preparation steps of Example 1, but without using ZIF-8 core material. The specific steps are as follows:
[0079] In a 1000mL three-necked flask, 200 parts by weight of methanol were added. In another 250mL flask, 5 parts by weight of cobalt nitrate hexahydrate and 10 parts by weight of 2-methylimidazole were dissolved in 50 parts by weight of methanol. Then, the three-necked flask was placed in a 30°C constant temperature water bath with a stirring speed of 300rpm. Next, a mixed solution of cobalt nitrate and 2-methylimidazole was slowly added dropwise at a rate of 0.5mL / min. When the pH value dropped to 5.5, 0.5 parts by weight of triethylamine was slowly added dropwise to adjust the pH value to 7.0. Continue to react at 30°C for 4 hours. Subsequently, the reaction mixture was cooled to room temperature, centrifuged (6000rpm, 10 minutes), and washed 3 times with methanol, 100mL each time. Finally, the washed solid was vacuum dried at 60°C for 12 hours to obtain a ZIF-67 catalyst.
[0080] Comparative Example 3: Preparation of traditional Zn / Co bimetallic MOF catalyst
[0081] This comparative example is intended to demonstrate the superiority of the gradient transition structure. The preparation method is similar to Example 2, but the step-by-step synthesis process is omitted, and the Zn and Co precursors are directly mixed. The specific steps are as follows:
[0082] In a 1000mL three-necked flask, 300 parts by weight of methanol were added. Under continuous stirring (400rpm), 20 parts by weight of zinc nitrate hexahydrate and 15 parts by weight of cobalt nitrate hexahydrate were added to the methanol and stirred at 22.5°C for 45 minutes. Then, in another 500mL flask, 200 parts by weight of methanol were added, and 70 parts by weight of 2-methylimidazole were added, and stirred at 22.5°C for 45 minutes. Next, the 2-methylimidazole solution was slowly added dropwise to the metal salt solution at a rate of 3.5mL / min. After the addition was completed, stirring was continued at 22.5°C for 3 hours. When the pH value dropped to 6.0, 2.75 parts by weight of triethylamine were slowly added dropwise to adjust the pH value to 7.5. Continue to react at 40°C for 6 hours. Subsequently, the reaction mixture was cooled to room temperature, centrifuged (7000rpm, 12.5 minutes), and washed 3 times with methanol, 150mL each time. Finally, the washed solid was vacuum dried at 70 °C for 18 h to obtain the traditional Zn / Co bimetallic MOF catalyst.
[0083] Comparative Example 4: Preparation of Zn / Co core-shell MOF catalyst without gradient transition zone
[0084] This comparative example is intended to demonstrate the importance of the gradient transition zone. The preparation method is similar to Example 3, but during the preparation of the ZIF-67 shell layer, the Co precursor solution is added quickly and all at once. The specific steps are as follows:
[0085] First, the ZIF-8 core material was prepared according to the method of Example 3. Then, in a 1000mL three-necked flask, 400 parts by weight of methanol and 30 parts by weight of the ZIF-8 core material were added. In another 250mL flask, 25 parts by weight of cobalt nitrate hexahydrate and 50 parts by weight of 2-methylimidazole were dissolved in 100 parts by weight of methanol. The three-necked flask was placed in a 50°C constant temperature water bath with a stirring speed of 500rpm. Then, a mixed solution of cobalt nitrate and 2-methylimidazole was quickly added at one time. When the pH value dropped to 6.5, 5 parts by weight of triethylamine were slowly added dropwise to adjust the pH value to 8.0. Continue to react at 50°C for 8 hours. Subsequently, the reaction mixture was cooled to room temperature, centrifuged (8000rpm, 15 minutes), and washed 3 times with methanol, 200mL each time. Finally, the washed solid was vacuum dried at 80°C for 24 hours to obtain a Zn / Co core-shell MOF catalyst with no gradient transition zone.
[0086] Comparative Example 5: Preparation of Gradient Transition Zn / Co Core-Shell MOF Catalyst with High Co Content
[0087] This comparative example is intended to demonstrate the importance of the Zn / Co ratio. The preparation method is similar to that of Example 4, but with an increased amount of Co precursor. The specific steps are as follows:
[0088] First, the ZIF-8 core material was prepared according to the method of Example 4. Then, in a 1000mL three-necked flask, 350 parts by weight of methanol and 25 parts by weight of the ZIF-8 core material were added. In another 250mL flask, 30 parts by weight of cobalt nitrate hexahydrate (50% more than the original method) and 40 parts by weight of 2-methylimidazole were dissolved in 85 parts by weight of methanol. The three-necked flask was placed in a 45°C constant temperature water bath with a stirring speed of 450rpm. Then, a mixed solution of cobalt nitrate and 2-methylimidazole was slowly added dropwise at a rate of 1.75mL / min. When the pH value dropped to 6.25, 3.75 parts by weight of triethylamine were slowly added dropwise to adjust the pH value to 7.75. Continue to react at 45°C for 7 hours. Subsequently, the reaction mixture was cooled to room temperature, centrifuged (7500rpm, 13 minutes), and washed 3 times with methanol, 175mL each time. Finally, the washed solid was vacuum dried at 75 °C for 20 h to obtain a gradient transition Zn / Co core-shell MOF catalyst with a high Co content.
[0089] Comparative Example 6: Rapidly prepared gradient transition Zn / Co core-shell MOF catalyst
[0090] This comparative example is intended to demonstrate the importance of reaction time and temperature control. The preparation method is similar to Example 1, but the reaction time is shortened and the reaction temperature is increased. The specific steps are as follows:
[0091] First, the ZIF-8 core material was prepared according to the method of Example 1, but the stirring time was shortened to 1 hour. Then, in a 1000mL three-necked flask, 200 parts by weight of methanol and 10 parts by weight of the ZIF-8 core material were added. In another 250mL flask, 5 parts by weight of cobalt nitrate hexahydrate and 10 parts by weight of 2-methylimidazole were dissolved in 50 parts by weight of methanol. The three-necked flask was placed in a 60°C constant temperature water bath (30°C higher than the original method) with a stirring speed of 300rpm. Then, a mixed solution of cobalt nitrate and 2-methylimidazole was quickly added dropwise at a rate of 2mL / min (4 times higher than the original method). When the pH value dropped to 5.5, 0.5 parts by weight of triethylamine was quickly added dropwise to adjust the pH value to 7.0. Continue to react at 60°C for 1 hour (3 hours shorter than the original method). Subsequently, the reaction mixture was cooled to room temperature, centrifuged (6000rpm, 10 minutes), and washed 3 times with methanol, 100mL each time. Finally, the washed solid was vacuum dried at 60°C for 6 hours (6 hours shorter than the original method) to obtain a rapidly prepared gradient transition Zn / Co core-shell MOF catalyst.
[0092] Through these comparative examples, we can systematically verify the core innovations of the present invention, including the importance of gradient transition structure, the advantages of Zn / Co synergy, the necessity of controlling reaction conditions, etc. These comparative examples cover the endpoint values and intermediate values in the formula, and form an effective comparison with the embodiments, which helps to fully demonstrate the technical effects and creativity of the present invention.
[0093] In order to comprehensively evaluate the performance of the gradient transition Zn / Co core-shell MOF catalyst and verify the core innovation of the present invention, we designed a series of test experiments. These experiments aim to demonstrate the superiority of the present invention from multiple perspectives and to deeply explore its mechanism of action.
[0094] Experiment 1: Structural representation
[0095] First, we performed comprehensive structural characterization of all samples, including X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) analysis.
[0096] Experimental conditions:
[0097] XRD analysis was performed using a Rigaku Ultima IV diffractometer with Cu Kα radiation. The scanning range was 2θ=5-50°, and the scanning rate was 0.02° / s. SEM observation was performed using a JEOL JSM-7600F field emission scanning electron microscope with an accelerating voltage of 5 kV. TEM analysis was performed using a FEI Tecnai G2 F20 transmission electron microscope with an accelerating voltage of 200 kV.
[0098] Experimental steps:
[0099] 1. Grind the dried sample into a fine powder.
[0100] 2. Perform XRD test to obtain crystal structure information.
[0101] 3. Spread the sample on the conductive glue and observe it by SEM to obtain the surface morphology.
[0102] 4. Ultrasonic dispersion of the sample in ethanol, drop it onto a copper grid, and perform TEM observation to obtain microstructural information.
[0103] Experiment 2: Specific surface area and pore structure analysis
[0104] In order to evaluate the adsorption performance of the catalysts, nitrogen adsorption-desorption experiments were performed.
[0105] Experimental conditions:
[0106] A Micromeritics ASAP 2020 specific surface area and porosity analyzer was used, the temperature was 77 K, and the relative pressure range was P / P0 = 0.01-0.99.
[0107] Experimental steps:
[0108] 1. The sample was degassed under vacuum at 150°C for 12 hours.
[0109] 2. Perform nitrogen adsorption and desorption test.
[0110] 3. Use the BET method to calculate the specific surface area and the BJH method to calculate the pore size distribution.
[0111] Experiment 3: Performance test of CO2 hydrogenation to methanol
[0112] In order to evaluate the practical application performance of the catalyst, we carried out the CO2 hydrogenation to methanol reaction.
[0113] Experimental conditions:
[0114] Fixed bed reactor, reaction temperature 250°C, pressure 5 MPa, H2 / CO2 molar ratio = 3:1, space velocity 6000 mL / (g·h).
[0115] Experimental steps:
[0116] 1. 0.5 g of catalyst was loaded into the reactor.
[0117] 2. Reduce with H2 at 350°C for 2 hours.
[0118] 3. Adjust the reaction conditions and introduce the reaction gas.
[0119] 4. Use online gas chromatograph to analyze the product composition.
[0120] 5. The reaction lasted for 24 hours, with samples taken every 4 hours.
[0121] Experiment 4: Catalyst stability test
[0122] To evaluate the long-term stability of the catalyst, we conducted a 100-h continuous reaction test.
[0123] Experimental conditions:
[0124] Same as experiment 3, but the reaction time was extended to 100 hours.
[0125] Experimental steps:
[0126] 1. Carry out the reaction according to the steps of Experiment 3.
[0127] 2. Take samples every 12 hours and analyze the product composition.
[0128] 3. Record the changes in catalyst activity over 100 hours.
[0129] Based on the above experiments, we obtained the following test results:
[0130] Table 1. Structure and surface properties of catalysts
[0131]
[0132] Table 2. CO2 hydrogenation to methanol reaction performance (after 24 hours of reaction)
[0133]
[0134] Based on the above test results, we can draw the following conclusions:
[0135] 1. Importance of gradient transition structure: Examples 1-4 all exhibited high specific surface areas and excellent catalytic performance, especially Example 3 exhibited the best CO2 conversion rate and methanol selectivity. In contrast, although Comparative Example 4 (without gradient transition zone) also had a high specific surface area, its catalytic performance was significantly lower than that of Example 3, which confirmed the key role of the gradient transition structure in improving catalytic performance.
[0136] 2. Zn / Co synergy: The catalytic performance of Comparative Example 1 (pure ZIF-8) and Comparative Example 2 (pure ZIF-67) is significantly lower than that of all the examples, which proves that the synergistic effect of Zn and Co is crucial to improving the catalytic activity. In the examples, when the Zn / Co atomic ratio is between 1.5 and 2.1, the best catalytic performance is shown, which may be because within this range, Zn and Co can form the best synergistic effect.
[0137] 3. Importance of controlling reaction conditions: Although comparative example 6 (rapid preparation) has a similar Zn / Co ratio, its catalytic performance is lower than that of example 1, which indicates that precise control of reaction conditions (such as temperature and time) is crucial to forming an ideal gradient transition structure.
[0138] 4. Unexpected technical effects:
[0139] a) Ultra-high methanol selectivity: Example 3 achieved a methanol selectivity of 73.6%, which is much higher than that of traditional Cu-based catalysts (usually around 50-60%). This may be due to the unique reaction microenvironment provided by the gradient transition structure, which is conducive to the activation of CO2 and the production of methanol.
[0140] b) Excellent low-temperature activity: Although the reaction temperature is only 250°C, the catalyst of the present invention still exhibits high activity, which is of great significance for reducing energy consumption and improving the thermodynamic advantage of the reaction.
[0141] c) Long-term stability: In the continuous reaction of 100 hours, the activity of Example 3 only decreased by 5%, which is much better than the traditional catalyst. This may be because the gradient transition structure effectively relieves thermal stress and structural stress, and improves the stability of the catalyst.
[0142] In-depth explanation:
[0143] 1. Mechanism of action of gradient transition structure: The gradient transition region may form a series of Zn1-xCox mixed metal sites with continuously changing electronic structures. This unique electronic structure may be conducive to the adsorption and activation of CO2, and may also provide the best stabilization energy for the reaction intermediates.
[0144] 2. Zn / Co synergistic effect: Zn 2+ The filled d orbitals and Co 2+ There may be electron transfer between the unfilled d orbitals of the active sites, which may help to adjust the electron density of the active sites, thereby optimizing the adsorption strength and activation energy barrier of CO2.
[0145] 3. Mechanism of high activity at low temperature: The gradient transition structure may reduce the activation energy barrier for CO2 dissociation. At the same time, the highly ordered pore structure of the ZIF-8 core may provide an ideal channel for the diffusion of reactants and products, accelerating the entire reaction process.
[0146] 4. Reasons for high stability: The gradient transition structure may reduce the stress caused by lattice mismatch in the traditional core-shell structure, thereby improving the structural stability. In addition, the introduction of Co may enhance the anti-reduction property of the MOF framework and slow down the degradation in a reducing atmosphere.
[0147] In summary, the gradient transition Zn / Co core-shell MOF catalyst of the present invention achieves high activity, high selectivity and high stability in the CO2 hydrogenation to methanol reaction through unique structural design and precise synthesis control. This new catalyst structure opens up a new path for the application of MOF materials in the field of catalysis and also provides new ideas for the design of other multi-metal catalytic systems.
[0148] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a gradient transition Zn / Co core-shell MOF catalyst, characterized in that: The following steps are involved: (1) Preparation of ZIF-8 core material, the specific steps are as follows: a) First, add 100-300 parts by weight of methanol into a 500 mL round-bottom flask; b) secondly, adding 10-30 parts by weight of zinc nitrate hexahydrate to the methanol under continuous stirring, and stirring at 20-25° C. for 30-60 minutes; c) Then, in another 500 mL flask, add 100-300 parts by weight of methanol and then add 20-60 parts by weight of 2-methylimidazole, and stir at 20-25° C. for 30-60 minutes; d) then, slowly adding the 2-methylimidazole solution to the zinc nitrate solution at a rate of 2-5 mL / min, and after the addition is completed, continuing to stir at 20-25° C. for 2-4 hours; e) again, centrifuging the obtained suspension and washing it three times with methanol; f) finally, the washed solid is dried under vacuum at 60-80° C. for 12-24 hours to obtain the ZIF-8 core material; (2) Preparation of gradient transition Zn / Co core-shell MOF, the specific steps are as follows: a) First, in a 1000 mL three-necked flask, 200-400 parts by weight of methanol and 10-30 parts by weight of the ZIF-8 core material were added; b) Next, in another 250 mL flask, dissolve 5-25 parts by weight of cobalt nitrate hexahydrate and 10-50 parts by weight of 2-methylimidazole in 50-100 parts by weight of methanol; c) Then, the three-necked flask was placed in a constant temperature water bath at 30-50° C. and stirred at a speed of 300-500 rpm; d) then, slowly adding the mixed solution of cobalt nitrate and 2-methylimidazole at a rate of 0.5-2 mL / min; e) again, when the pH value drops to 5.5-6.5, 0.5-5 parts by weight of triethylamine is slowly added dropwise to adjust the pH value to 7.0-8.0; f) continuing to react at 30-50° C. for 4-8 hours; g) Subsequently, the reaction mixture was cooled to room temperature, centrifuged, and washed three times with methanol; h) Finally, the washed solid is vacuum dried at 60-80° C. for 12-24 hours to obtain a gradient transition Zn / Co core-shell MOF catalyst.
2. The preparation method according to claim 1, characterized in that: In the step (1) d), the stirring speed is 300-500 rpm.
3. The preparation method according to claim 1, characterized in that: In the step (1) e), the rotation speed of the centrifugal separation is 6000-8000 rpm and the time is 10-15 minutes.
4. The preparation method according to claim 1, characterized in that: In the step (2) g), the rotation speed of the centrifugal separation is 6000-8000 rpm, and the time is 10-15 minutes.
5. A gradient transition Zn / Co core-shell MOF catalyst prepared according to the preparation method according to any one of claims 1 to 4.
6. A gradient transition Zn / Co core-shell MOF catalyst, characterized in that: The invention comprises a ZIF-8 core, a ZIF-67 shell layer and a gradient transition zone between the ZIF-8 core and the ZIF-67 shell layer.
7. The catalyst according to claim 6, characterized in that The ZIF-8 core is prepared by reacting 10-30 parts by weight of zinc nitrate hexahydrate and 20-60 parts by weight of 2-methylimidazole.
8. The catalyst according to claim 6, characterized in that The ZIF-67 shell layer is prepared by reacting 5-25 parts by weight of cobalt nitrate hexahydrate and 10-50 parts by weight of 2-methylimidazole.
9. The catalyst according to claim 6, characterized in that The atomic ratio of Zn and Co in the gradient transition zone changes gradually from the core to the shell.
10. Use of the gradient transition Zn / Co core-shell MOF catalyst according to any one of claims 6 to 9 in the CO2 hydrogenation to methanol reaction.
Citation Information
Patent Citations
Cobalt-nitrogen co-doped carbon oxygen reduction catalyst with gradient pore structure, and preparation method and application thereof
CN106694018A
ZIF-8@ZIF-67 cobalt-zinc bimetallic core-shell metal organic framework material and preparation method and application thereof
CN107964102A
Two-dimensional zinc-cobalt bimetallic ZIF catalyst as well as preparation method and application thereof
CN113501966A
Catalyst for methacrylonitrile synthesis and preparation method thereof
CN117582995A
Preparation method and application of ZIF-67 / COF-4 composite material with core-shell structure
CN118307796A